Determination of the lateral collection length of charge carriers for silver-nanowire-electrode-based Cu(In, Ga)Se2 thin-film solar cells. (1st March 2019) - Lee, Sangyeob; Jang, Jiseong; Cho, Kyung Soo; Oh, Yong-Jun; Hong, Ki-Ha; Song, Soomin; Kim, Kihwan; Eo, Young-Joo; Ho Yun, Jae; Gwak, Jihye; Chung, Choong-Heui
Highlights: Lateral collection length is important for network-electrode-based solar cells. A method to determine the lateral collection length is developed. The lateral collection length for Cu(In, Ga)Se2 solar cells was 26 μm under 1-sun. The method can be aaplied to other solar cells with network-transparent-electrodes. Abstract: Silver nanowire (AgNW) electrodes have been employed in solar cells as transparent conducting electrodes (TCEs). When a AgNW electrode is used as a network-type TCE in solar cells, photogenerated charge carriers must laterally travel to reach AgNW networks. If the empty space of the network is larger than the lateral collection length of the charge carriers ( L lc ), a significant fraction of the charge carriers will be lost. Therefore, determination of L lc is essential for choosing and/or designing a suitable network for solar cells. Here, we develop a method to relate the lateral photocurrent measured from a specially designed pattern to the L lc value. We apply this method to Cu(In, Ga)Se2 thin-film solar cells with AgNW TCEs. The L lc value was determined to be ≈ 26 μm in the CdS/CIGS/Mo structure under 1-sun illumination. The measured lateral collection length is much larger than the normal spacing between AgNWs, indicating a high lateral collection efficiency in AgNW TCE-based CIGS thin-film solar cells.